Crossing the peninsula: The role of Noh Bec, Yucatán, in ancient Maya Classic Period population dynamics from an analysis of dental morphology and Sr isotopes. Issue 6 (19th June 2015) - Cucina, Andrea; Price, T. Douglas; Magaña Peralta, Evelia; Sierra Sosa, Thelma; Gurri, Francisco D.; Ortega‐Muñoz, Allan
<x xml:space="preserve">Abstract</x> Objectives This article aims to infer population dynamics in the Noh Bec region (Yucatán Peninsula, México) during the Maya Classic period (AD 350–800), based on a combined analysis of dental morphology and 87Sr/86Sr isotopes, and on a comparison of the dental evidence together with archaeological signs of trade and relationships with other regions in the Maya world. Methods Twenty‐three dental morphological variables were used to estimate affinities between dental collections from Noh Bec and 10 more sites from the region. 87Sr/86Sr isotopes were recorded from the enamel of permanent teeth of 32 individuals from Noh Bec, and compared to the site's local chemical signature. Results Dental morphology reveals a strong affinity with Kohunlich, in the central Maya lowlands, while some diversity can be noted with the Petén sites (such as Calakmul) as well as sites on the northern coast of the peninsula. The local extent of 87Sr/86Sr variation ranges between 0.7086 and 0.7088. Eight of the 32 Noh Bec individuals analyzed were born elsewhere. Isotopic values indicate different places of origin although apparently none were from the northern coast of the peninsula; instead, the range of variability reflects many locations along the western coast of the peninsula as well as inland sites in the Chenes region in Campeche. Conclusions Dental morphology and 87Sr/86Sr ratios indicate intense population dynamics in the peninsula during the Maya Classic period. Despite the different nature of the dental and isotopic indicators, results agree with archaeological evidence and with proposed trade routes in the peninsula. Am. J. Hum. Biol. 27:767–778, 2015. © 2015 Wiley Periodicals, Inc.